FOXI1 immunohistochemistry differentiates benign renal oncocytoma from malignant chromophobe renal cell carcinoma - Molnár, Ágnes; Kovacs, Gyula (Anticancer research, 2019)
Background/Aim: Renal oncocytoma (RO) and chromophobe renal cell carcinoma (chRCC) are suggested to develop from α- and β-intercalated (IC) cells of the collecting duct expressing solute carrier family 4 member 1 (SLC4A1) and SLC26A4 under control of forkhead box 1 (FOXI1) transcription factor. The aim of this study was to clarify the possible cellular origin and of RO and chRCC. Materials and Methods: Immunohistochemistry for aquaporin 2 (AQP2), FOXI1, SLC4A1 and SLC16A4 was applied to distinct types of renal cell tumors. Results: Nuclear FOXI1 staining occurred in 96% of 83 ROs, in 3% of 90 chRCCs and none of the other tumor types. The α-IC cell marker SLC4A1 was seen in 60% of RO and 11% of chRCC, whereas staining for the β-IC cell marker SLC26A4 was negative in all but one tumor. Conclusion: Although the origin of RO remains unclear, our findings suggest that FOXI1 immunohistochemistry is useful in differential diagnosis of RO from chRCC with overlapping histology.
accepted May 23, 2019
Gesehen am 30.01.2020